2022
DOI: 10.1186/s44158-022-00049-4
|View full text |Cite
|
Sign up to set email alerts
|

Early management of patients with aneurysmal subarachnoid hemorrhage in a hospital with neurosurgical/neuroendovascular facilities: a consensus and clinical recommendations of the Italian Society of Anesthesia and Intensive Care (SIAARTI)—part 2

Abstract: Background Questions remain on the optimal management of subarachnoid hemorrhage (SAH) patients once they are admitted to the referring center, before and after the aneurysm treatment. To address these issues, we created a consensus of experts endorsed by the Italian Society of Anesthesia and Intensive Care (SIAARTI) to provide clinical guidance regarding this topic. Specifically, in this manuscript (part 2), we aim to provide a list of experts’ recommendations regarding the management of SAH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…8 CTA was the most frequently used modality to confirm the presence of cerebral vasospasm as the cause of DNDs related to DCI, in agreement with the recommendations of several consensus conferences. 13,14 Transcranial Doppler/cerebral ultrasound is the most frequently used diagnostic tool for cerebral vasospasm in comatose aSAH patients or in aSAH patients unable to tolerate an interruption in sedation (e.g., those with intracranial hypertension). Neurological examination is also commonly used in comatose aSAH patients or in aSAH patients unable to tolerate an interruption in sedation; this approach is logical and reasonable in the former scenario but unreliable in the latter scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 CTA was the most frequently used modality to confirm the presence of cerebral vasospasm as the cause of DNDs related to DCI, in agreement with the recommendations of several consensus conferences. 13,14 Transcranial Doppler/cerebral ultrasound is the most frequently used diagnostic tool for cerebral vasospasm in comatose aSAH patients or in aSAH patients unable to tolerate an interruption in sedation (e.g., those with intracranial hypertension). Neurological examination is also commonly used in comatose aSAH patients or in aSAH patients unable to tolerate an interruption in sedation; this approach is logical and reasonable in the former scenario but unreliable in the latter scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents mainly utilized induced hypertension as the first step in the management of DCI related to vasospasm and intra-arterial procedures as the second step; this approach follows recommendations in several guidelines. 9,10,13,14 However, data are lacking regarding the optimal timing of intra-arterial procedures, particularly in patients receiving vasopressors for DCI related to vasospasm; little is known whether intra-arterial procedures should be performed before, at the same time as, or after failure of vasopressor therapy. Noradrenaline was the most used vasopressor.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that current guidelines suggest that patients with SAH are managed trying to keep them awake as much as possible to early detected a possible clinical deterioration (i.e., vasospasm) through assessment of sequential neurological examinations during ICU stay. This may impact on earlier extubation and reduced days of mechanical ventilation, thus decreasing the risk of developing VAP [ 25 27 ]. In our cohort, we observed that only 3% of patients with ischemic stroke developed VAP, which is lower than reported in previous studies (4–57%) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rates of our patients on days 30 th and 90 th after ictus were also lower than rates reported in previous studies (22–25% and 25–29%, respectively) [ 38 , 39 ]. These findings might be due to several advances in the past decades in the medical diagnosis and care of patients with aneurysmal SAH, including medical advances, new systems of standardized care in neurocritical care units, and new surgical and endovascular techniques for aneurysmal SAH [ 4 , 40 ]. Additionally, as unique to patients with aneurysmal SAH in Vietnam, many are not transferred to a central hospital and are relegated to death in the local hospitals as well as dying outside of the hospital [ 41 ].…”
Section: Discussionmentioning
confidence: 99%